Contextualizing change in Turkish foreign policy: the promise of the 'two-good' theory. Issue 1 (2nd January 2016) - Hatipoglu, Emre; Palmer, Glenn
Abstract : The level of activism in Turkey's foreign policy has reached unprecedented levels during the country's modern history. This increased activism contrasts starkly with Turkey's characteristically traditional status quo orientation evinced during the Cold War. This study aims to establish a theoretical foundation to explain this multifaceted change in Turkish foreign policy. In doing so, it contends that the 'two-good' theory of foreign policy renders considerable analytical leverage for contextualizing recent changes in Turkish foreign policy. The theory posits that change in a country's foreign policy is contingent upon its willingness and capability to actively promote its interests. Furthermore, the 'two-good' theory postulates the method a country might employ to implement its foreign policy is a function of these two factors as well. The theory leads to two testable hypotheses regarding Turkish foreign policy. This study supports these hypotheses with qualitative and quantitative evidence.